STUDI MITIGASI GEMPA DI BENGKULU DENGAN MEMBANGUN RUMAH TAHAN GEMPA - Fepy Supriyani (Universitas Bengkulu, 2018)
Bengkulu province lies on earthquake hazard zone where light and moderate earthquake often occur in relatively high frequency, due to geographical position of the province which is between 2 earthquake belts, Mentawai fault in Indian Ocean on Indo Australia tectonic plate and Sumatra fault around Bukit Barisan. Building failures due to earthquake mostly occur on residential structures. Although failures and damages due to earthquake generate major impact on residential structures, no lesson on the importance of mitigation by applying earthquake resistant structures on residential buildings is learned yet. Typical residential structures failures or damages that occur in Bengkulu city is mostly on engineered and non engineered brick wall. Since no available method of earthquake event prediction, hence mitigation is more important in order to prevent major loss and disaster any further. Hence socialization on earthquake and earthquake resistant structures/houses particularly on structural failure and damages that occurred in Bengkulu to the community is needed, also to transfer knowledge to the community about how to prepare residential buildings in earthquake hazard zones. By providing practical guidance about earthquake resistant residential buildings, socialization and technical training for construction workers, it is expected that the actions are able to assist the community to construct their residential buildings that comply to earthquake resistance standards and suits the particular needs of local residents, hence minimizing the effect of loss due to earthquake, usually defined as earthquake mitigation. Earthquake resistant residential buildings must comply standards ofmaterial and construction method.